Intracellular Delivery of Natural Antioxidants via Hyaluronan Nanohydrogels - Elita Montanari; Chiara Di Meo; Tommasina Coviello; Virginie Gueguen; Graciela Pavon-Djavid; Pietro Matricardi (MDPI AG, 2019)
Natural antioxidants, such as astaxanthin (AX), resveratrol (RV) and curcumin (CU), are bioactive molecules that show a number of therapeutic effects. However, their applications are remarkably limited by their poor water solubility, physico-chemical instability and low bioavailability. In the present work, it is shown that self-assembled hyaluronan (HA)-based nanohydrogels (NHs) are taken up by endothelial cells (Human Umbilical Vein Endothelial Cells, HUVECs), preferentially accumulating in the perinuclear area of oxidatively stressed HUVECs, as evidenced by flow cytometry and confocal microscopy analyses. Furthermore, NHs are able to physically entrap and to significantly enhance the apparent water solubility of AX, RV and CU in aqueous media. AX/NHs, RV/NHs and CU/NHs systems showed good hydrodynamic diameters (287, 214 and 267 nm, respectively), suitable ζ-potential values (−45, −43 and −37 mV, respectively) and the capability to neutralise reactive oxygen species (ROS) in tube. AX/NHs system was also able to neutralise ROS in vitro and did not show any toxicity against HUVECs. This research suggests that HA-based NHs can represent a kind of nano-carrier suitable for the intracellular delivery of antioxidant agents, for the treatment of oxidative stress in endothelial cells.